Evaluation of subsidence using Asaoka's method; an inverse approach to the problem - Galagoda, Herath Mudiyanselage Mahinda Bandara; Ohta, Hideki; Tomiolo, Andrea; Jerasak Premchitt; Royal Netherland Government (Bangkok : Asian Institute of Technology, 1981)
An attempt which was made to predict soil layer compression due to ground water withdrawal in Bangkok area, is presented here. In this study a newly developed method An Observational Procedure of Settlement Prediction proposed by ASAOKA(1978), was incorporated thus avoiding the necessity of soil parameters and complex boundary conditions. Beforehand, the validity of the method was verified by applying it to settlement records from two embankment constructed in Bangkok area. The rate of compression and the compression of the soil layers down to very large depths were predicted for the next 8 years. The results show more than 0.5m. compression within next 5 years, if the present rate of ground water withdrawal continues.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1981